Hodgkin lymphoma and PD-1 blockade: an unfinished story - Merryman, Reid; Armand, Philippe (Annals of Lymphoma, 2017)
Classical Hodgkin lymphoma (cHL) is characterized genetically by near-universal alterations in 9p24.1, which result in constitutively increased expression of programmed cell death 1 (PD-1) receptor ligands on malignant Reed-Sternberg (RS) cells and evasion of immune destruction. Based on this genetic susceptibility, anti-PD-1 monoclonal antibodies have been tested in patients with relapsed or refractory (R/R) cHL and have shown impressive response rates and durable remissions, leading to the accelerated approval of two PD-1 inhibitors in this setting, nivolumab and pembrolizumab. These drugs have changed the clinical trial landscape for cHL. PD-1 blockade is now being tested in virtually every phase of treatment with the goal of capitalizing on its benefit earlier in a patient’s treatment course. In addition, based on its tolerability and single agent activity, PD-1 inhibitors are being paired with many other agents including chemotherapy and immunotherapy. Early experience combining PD-1 inhibitors with ipilimumab or brentuximab suggests that this strategy is feasible, but longer-term follow-up is necessary to determine the true benefit of these combinations. Given the numerous possible combination partners, a better understanding of the mecha-nisms of primary and acquired resistance will be important to rationally design trials of drug combinations that include PD-1 inhibitors. Finally, early clinical data suggests that treat-ment with PD-1 blockade in conjunction with allogeneic hematopoietic stem cell transplant (HSCT) (either prior to transplantation or for relapse after transplantation) may be asso-ciated with an increased risk of immunologic complications, but also the potential for a synergistic anti-cancer effect. Ongoing investigation is necessary to guide treatment strategies to minimize toxicity and maximize efficacy in this setting. While initial trials of PD-1 inhibitors in cHL were met with much excitement, additional investigation is nec-essary to determine how anti-PD-1 therapy will be optimally incorporated into the treatment paradigm for patients with cHL.